THE IMPACT OF DOMESTIC VIOLENCE ON THE LEARNING PROCESS OF HIGH SCHOOL STUDENTS - Mbogo, Rosemary Wahu (Advances in Social Sciences Research Journal, 2018)
Exposure to domestic violence among high school learners is one critical issue in schools that needs to be brought at the forefront in understanding dynamics involved and its impact on the learning process. A range of effects not limited to decreased educational performance and behavioural problems arise from domestic violence. Mistakenly, most people fail to see the harm caused to a child living in an abusive household unless physical abuse is extended towards them. Authors of this paper recognize the impact, other than physical, and explore how domestic violence affects the learning process of students in high school. A descriptive design was adopted for the study. With focus in Migwani Sub-county, schools were stratified into two, i.e. girls’ and boys’ schools. A sample of 56 respondents was then conveniently obtained from 10 public schools. This included students (30), teachers (12), principals (10) and parents (4). Questionnaires and interviews were used to collect data. Data were analysed using the SPSS. The paper presents the perceptions of respondents on domestic violence as the causative agent of sluggishness on learning in Migwani Sub-county. The study is meant to better the learning process in the County.